Design, implementation and testing of a set of task-based strategies to improve EFL reading comprehension skills targeted to A2.2 level students attending a public urban high school. - Salvador Pacheco, Bertha Paola (2018)
This study presents the testing of a set of task-based strategies in teaching reading in a four-month period. Each month three strategies were taught and used by the students in the study: one at the pre-reading stage, one at the while-reading stage, and one at the post-reading stage. It was applied to a group of 21 students attending first year of bachillerato in a public school in Cuenca, Ecuador. Their ages were between 15 and 17 and their level of English was A2.2. The main purpose of this study was to determine if after working with pre-, while- and post-reading task-based strategies, the students could improve their reading comprehension skills. Moreover, scaffolding accompanied the selected strategies to verify if it could be another important factor that could contribute to reading comprehension ability. The methodology included the qualitative method through observational field notes; the researcher collected information in order to determine whether scaffolding benefited students who were developing comprehension skills and to check if it was possible to remove it progressively in order for these students to gain autonomy. The methodology also included the quantitative method: two surveys were applied; one before the testing period and one after it to know to what extent students knew about task-based reading strategies and to learn their perceptions in relation to the strategies they worked with. Furthermore, quizzes were given to students to assess reading comprehension. The results based on the qualitative data revealed scaffolding is an important component to develop reading comprehension. The analysis of the quantitative data showed that all the students, at different levels, improved their reading comprehension ability after the four-month term. Consequently, reading is an activity that needs strategies to be mastered, and the support of the teacher is important for students to achieve improvement and to gain autonomy.